Evaluasi Implementasi Clinical Pathway Sectio Caesarea di RSUD Panembahan Senopati Bantul - Yurni Dwi Astuti; Arlina Dewi; Merita Arini (Universitas Muhammadiyah Yogyakarta, 2017)
The purpose of this study was performed to evaluate the content and quality of clinical pathway sectio Caesarea (CP SC), compliance evaluate the implementation of CP SC and know that there are barriers in the implementation of CP SC, so it can make recommendations to improve the implementation of CP SC in hospitals Panembahan Senopati Bantul. The research used mix method focusing in case study design at obsgyn unit room in Panembahan Senopati State Hospital in Bantul. Sample of respondent to the quantitative data to observe at the documentation and obedience to the medical records of patients who had been operated sectio caesarea’s elective that choosen by total sampling and evaluation of CP SC using the Integrated Care Pathway Appraisal Tools (ICPAT) consisting of six dimensi. Data qualitative is obtained by do a deep interviews with a purposive sampling method.